2014
DOI: 10.14569/ijacsa.2014.050609
|View full text |Cite
|
Sign up to set email alerts
|

Principle of Duality on Prognostics

Abstract: Abstract-The accurate estimation of the remaining useful life (RUL) of various components and devices used in complex systems, e.g., airplanes remain to be addressed by scientists and engineers. Currently, there area wide range of innovative proposals put forward that intend on solving this problem. Integrated System Health Management (ISHM) has thus far seen some growth in this sector, as a result of the extensive progress shown in demonstrating feasible and viable techniques. The problems related to these te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Hence, a unifying model is what we might be able to benefit from in mapping failure pattern of a converter to the basic unified models; and ultimately, creating similarity-based prognostics models. It is shown that prognostics and failure pattern of a Cuk converter can be applied to its dual circuit [20].…”
Section: A Dc-dc Convertermentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, a unifying model is what we might be able to benefit from in mapping failure pattern of a converter to the basic unified models; and ultimately, creating similarity-based prognostics models. It is shown that prognostics and failure pattern of a Cuk converter can be applied to its dual circuit [20].…”
Section: A Dc-dc Convertermentioning
confidence: 99%
“…From system level prognostics, changes in the energy transfer in Cuk converter can be used to detect earlier sign of degradation and failure. In fact, as a result of degradation, energy is not sufficiently transferred in the circuit [20].…”
Section: A Dc-dc Convertermentioning
confidence: 99%